The Development of the Laboratory
XVI, 260 p. 24 illus.
Keywords: Laboratories are fundamental to the practice of science, yet there is a paucity of serious historical analysis of the subject. This book sets out to reflect the diversity in the variety of laboratories in existence and the multiplicity of their development.